Switchable ETFE façades: A study on the thermo-optical, daylighting and energy performance of climate adaptive building envelopes - Flor, Jan-Frederik (2021)
The development of transparent, light, flexible, and resistant materials like ethylene tetrafluoroethylene (ETFE) foil allows rethinking the function of the building envelope as an interactive and moderating membrane between the internal and external environment. Air inflated ETFE foil constructions, forming pneumatic cushions, are structurally efficient and have increasingly been used in state-of-the-art architecture. However, the prediction of the thermo-optical behaviour of ETFE structures in building façades is a challenge for designers and manufacturers. The proposal of adaptive or switchable systems, which can be modified on demand to respond to changing climate conditions, is a recent technological answer to that challenge. Nevertheless, the understanding of the impact of switchable ETFE façades on the energy and daylighting performance of buildings, as well as on comfort and user experience, is still limited and represents a barrier to large scale implementation. In this research switchable multi-layer ETFE cushions were investigated through a series of independent but interrelated studies, using ray-tracing, energy simulations and virtual reality, to assess daylighting qualities, energy performance and view perception of spaces enclosed with switchable ETFE façades. The main findings of the conducted studies revealed the superior energy and daylighting performance of spaces enclosed by switchable ETFE cushions. In comparison to static ETFE cushions and standard double glazing, climate adaptive switchable systems actively reduce solar gains and improve the environmental performance of the building envelope. Implications on energy consumption and natural daylighting of the enclosed spaces are of relevance for future applications in building façades: Glare reductions of 59% and an increase of useful daylight illuminance of 58%, with annual energy savings of up to 56% were predicted in this thesis. However, the study revealed that view clarity of foils, print inks, and patterns of current switchable ETFE cushions is not yet satisfactory and remains a challenge for future research and development. It is expected that the outcomes of this research will contribute to advancements in ETFE-foil façade technology, that may lead to energy savings in the building sector and support the agenda against climate change.